Effect of technological properties of pea seeds and processing modes on dehulling efficiency - Kharchenko, Yevgen; Sharan, Andrii (My University, 2023)
The process of dehulling grain peas is the most important technological operation of groats of pea seeds. This paper presents the results of the study of the process of dehulling of pea seeds, which allow to understand the behavior of pea seeds during its dehulling in machines with abrasive working bodies. It is determined that the increase of processing time, the pea seeds, the speed of the working organs and filling coefficient of the working chamber of the dehuller increase the efficiency of dehulling peas by linear dependence. Increase in the size of pea seeds contributes to increase of efficiency of dehulling mainly due to increase of the yield of small. The increase in the scale of seeds leads to a decrease in the dehulling index. Along with the increasing efficiency of dehulling, increases and yield of trinkets at the expense of the kernel. With the increase in the moisture of pea seeds, the yield of a fine grits increases compared to the dehulling of dry pea. Yield of the kernel is directly proportional to the reduction of the yield of undehulling seeds. The yield of a fine grits also has linear dependencies when you change the following parameters. In the process of dehulling reduces the ash content of the kernel, but also decreases the ash content and husk and dust middlings, which is the result of transition of low-ash content particles of kernel into the dust middlings

Процес лущення зерна гороху є найважливішою технологічною операцією крупи насіння гороху. У даній роботі представлені результати дослідження процесу лущення насіння гороху, які дозволяють зрозуміти поведінку насіння гороху під час його лущення в машинах з абразивними робочими органами. Визначено, що збільшення часу обробки насіння гороху, швидкості робочих органів та коефіцієнта заповнення робочої камери лущильника підвищує ефективність лущення гороху за лінійною залежністю. Збільшення розміру насіння гороху сприяє підвищенню ефективності лущення головним чином за рахунок збільшення врожаю дрібного. Збільшення окалини насіння призводить до зниження індексу лущення. Разом зі збільшенням ефективності лущення, збільшується і вихід дрібничок за рахунок ядра. Із збільшенням вологості насіння гороху вихід дрібної крупи підвищується порівняно з лущенням сухого гороху. Урожайність ядра прямо пропорційна зменшенню врожаю нелущеного насіння. Вихід дрібної крупки також має лінійну залежність при зміні наступних параметрів. У процесі лущення зменшується зольність ядра, а також зменшується зольність і вміст лушпиння і пилу, що є результатом переходу малозольних частинок ядра в пиловий промпродукт.
Keywords: кафедра технології зберігання і переробки зерна; лущильник; peeler; горох; pea; індекс лущення